Barriers and measures to improve adoption of irrigation technologies: A case study from the Bundaberg region in Queensland, Australia. (22nd February 2021) - Koech, Richard; Haase, Michelle; Grima, Bree; Taylor, Benjamin
Abstract: Australia is the driest continent and is largely reliant on irrigation for efficient agricultural production. Irrigation uses significant volumes of water, and in recent decades many initiatives have been undertaken to improve efficiencies of irrigation systems and management practices. This paper analyses the perceptions and barriers to adoption of irrigation technologies and management practices in agriculture based on a field study undertaken in the Bundaberg region in Queensland, Australia. Overall, most farmers surveyed rated the efficiency of their irrigation systems very highly; nonetheless, more than half the farmers surveyed recognized that their systems and practices had the potential for further improvement through automation. Financial constraints and uncertainty around the economic viability of investing in certain agricultural technologies emerged as major barriers to adoption of available and emerging technologies that could improve irrigation efficiency. This is occasioned by insufficient evidence of the benefits of adopting these innovations. Issues suggested by the respondents for further extension, development and research align closely to known barriers to adoption of agricultural innovations. A key finding and recommendation of this study is that farm‐specific cost–benefit analyses of new irrigation technologies and practices are required to facilitate the decision‐making process for the improvement of irrigation efficiency. Résumé: L'Australie est le continent le plus sec et dépend largement de l'irrigation pour une production agricole efficace. L'irrigation utilise des volumes d'eau importants et, au cours des dernières décennies, de nombreuses initiatives ont été prises pour améliorer l'efficacité des systèmes d'irrigation et des pratiques de gestion. Cet article analyse les perceptions et les obstacles à l'adoption des technologies d'irrigation et des pratiques de gestion en agriculture sur la base d'une étude de terrain entreprise dans la région de Bundaberg dans le Queensland, en Australie. Dans l'ensemble, la plupart des agriculteurs interrogés ont très bien évalué l'efficacité de leurs systèmes d'irrigation; néanmoins, plus de la moitié des agriculteurs interrogés ont reconnu que leurs systèmes et leurs pratiques pouvaient encore être améliorés grâce à l'automatisation. Les contraintes financières et l'incertitude entourant la viabilité économique de l'investissement dans certaines technologies agricoles sont apparues comme des obstacles majeurs à l'adoption des technologies disponibles et émergentes susceptibles d'améliorer l'efficacité de l'irrigation. Cela est dû à des preuves insuffisantes des avantages de l'adoption de ces innovations. Les questions suggérées par les répondants pour une vulgarisation, un développement et une recherche supplémentaires s'alignent étroitement sur les obstacles connus à l'adoption d'innovations agricoles. Une des principales conclusions et recommandations de cette étude est que des analyses coûts‐avantages spécifiques à l'exploitation des nouvelles technologies et pratiques d'irrigation sont nécessaires pour faciliter le processus de prise de décision pour l'amélioration de l'efficacité de l'irrigation.